The unsettled settler: personal and discursive tragedy in Alexandra Fuller's memoirs - Scott, Skye (Department of English Language and Literature, 2023)
Alexandra Fuller's memoirs detail the lives of white settlers in Southern Africa (specifically Zimbabwe) from white-rule to post-independence. Her memoirs illustrate how the settler colonial dream of the promised land in Africa would ultimately fail to be fully realised and maintainable. Yet, through the portrayal of unexamined colonial discourse, Fuller continues to perpetuate a constructed notion of Africa. The publication of her first memoir, Don't Let's Go to the Dogs Tonight, coincided with international media coverage of President Robert Mugabe's contested land redistribution programme and told a similar story of the loss of their family farm. Written from her home in Wyoming in the United States, Fuller's work forms part of a white expatriate culture that writes home to Africa from a different continent. Previous works have failed to address the theme of settler colonialism in literature specifically pertaining to the field of Southern African literature. This dissertation makes use of a postcolonial framework to examine Alexandra Fuller's work; Don't Let's Go to the Dogs Tonight: An African Childhood, Scribbling the Cat: Travels with an African Soldier and Cocktail Hour under the Tree of Forgetfulness. Fuller's memoirs are used to explore the function of innocence, nostalgia and memory in postcolonial white writing, the construction of whiteness and masculinity in Africa and the tragedy of discourse that is still pervasive in the portrayal of colonial notions of Africa as a playground for disaffected Westerners. Fuller's writing forms part of a Zimbabwean post-independence body of work that absolves whiteness of complicity and a history of colonial violence. Fuller's memoirs ultimately do not settle on a definitive point about Zimbabwe and its history of colonial dispossession or herself and settler colonial family.